Absorption Properties of Co-Ce Codoped TiO2/SiO2/NiFe2O4 Mesoporous Microspheres - Ouyang, Zhaohui; Wu, Lin; Yi, Delian (Asian Journal of Chemistry, 2013)
By using nanoparticles NiFe2O4 as magnetic carrier, the polystyrene-SiO2/NiFe2O4 magnetic microspheres were prepared from styrene, tetraethoxysilane, by emulsion polymerization using 3-methacryloxypropyltrimethoxysilane as a cross-linking agent. (Co,Ce)-TiO2/SiO2/NiFe2O4 multilayer magnetic mesoporous microspheres material were prepared by sol-gel process with tetrabutyl titanat as raw materials Co, Ce as codoped agent, PS-SiO2/NiFe2O4 particle as the core, sodium dodecyl sulphate and polyvinylpyrrolidone as templating agent. The complex permittivity and permeability of composites made from (Co, Ce)-TiO2/SiO2/NiFe2O4 multilayer magnetic mesoporous microspheres material embedded in paraffin matrix separately are measured by voter network analyzer and the reflectivity is calculated within 1-18 GH. The absorption mechanisms of magnetic mesoporous microspheres material are studied based on the electromagnetic wave propagation laws in lossy medium. The microwave absorption properties of the multilayer composite film are excellent. The maximum microwave loss efficiency reaches 31 dB and the continuous frequency range with the loss above 20d B reaches 2 GHz.